Unlocking the Potential of Lignocellulosic Biomass Dragon Fruit (Hylocereus polyrhizus) in Bioplastics, Biocomposites and Various Commercial Applications - Taharuddin N.H.; Jumaidin R.; Mansor M.R.; Hazrati K.Z.; Tarique J.; Asyraf M.R.M.; Razman M.R. (MDPI, 2024)
Dragon fruit, also called pitaya or pitahaya, is in the family Cactaceae. It is found in two genera: Selenicereus and Hylocereus. The substantial growth in demand intensifies dragon fruit processing operations, and waste materials such as peels and seeds are generated in more significant quantities. The transformation of waste materials into value-added components needs greater focus since managing food waste is an important environmental concern. Two well-known varieties of dragon fruit are pitaya (Stenocereus) and pitahaya (Hylocereus), which are different in their sour and sweet tastes. The flesh of the dragon fruit constitutes about two-thirds (~65%) of the fruit, and the peel is approximately one-third (~22%). Dragon fruit peel is believed to be rich in pectin and dietary fibre. In this regard, extracting pectin from dragon fruit peel can be an innovative technology that minimises waste disposal and adds value to the peel. Dragon fruit are currently used in several applications, such as bioplastics, natural dyes and cosmetics. Further research is recommended for diverging its development in various areas and maturing the innovation of its usage. 2023 by the authors.